IRREGULAR MENSTRUATION THERAPY WITH ACUPUNCTURE, POMEGRANATE PEEL AND GINGER HERBS - Sinta Diyah Dimyati; Suhariningsih Suhariningsih; Nurmawati Fatimah (Journal of Vocational Health Studies)
Background: Menstruation is the process of regular discharging of blood in women. The menstrual cycle describes the distance between the first day of menstruation and the next menstruation which normally occurs within 28-35 days. According to Traditional Chinese Medicine, the menstrual cycle is used as a simple diagnostic way in viewing a woman's fertility status. Purpose: To determine the effect of acupuncture combination therapy at the Taichong (LV3), Sanyinjiao (SP6), Diji (SP8) and Qihai (CV6) point with herbal pomegranate peel (Punica granatum L.) and ginger (Zingiber officinale Rosc.) in irregular menstrual patients. Methods: Treatment of irregular menstruation with acupuncture and herbal therapy methods. Acupuncture therapy is carried out at the Taichong (LV3), Sanyinjiao (SP6), Diji (SP8) and Qihai (CV6) point with the principle of helping to smooth out the flow of Qi and regulating the Chong & Ren vessels. In herbal therapy the patient is given decoction of herbal pomegranate peel (Punica granatum L.) and ginger (Zingiber officinale Rosc.). Results: Therapy using acupuncture and herbs to handling cases of irregular menstruation showed a good change in patient's menstrual cycle, this can make the patient's menstrual cycle after therapy to 36 days, which is almost closer to normal compared to before therapy with menstrual cycles exceeding 40 days. Conclusion: Acupuncture and herbal therapy can be continued so that the patient's menstrual cycle returns to normal.